A Comparative Study of the Punishments and related Teachings about adultery in World Religions - Khan, Abzahir; Adil, Muhammad (Journal of Islamic and Religious Studies, 2017)
Acquisition of peace, eradication of crimes and cleaning a society of all immoral activities is the basic and equal need of all human beings without any differentiation of any worldly and divine religions, on the basis of this need, Imam Ghazali declared “peace” is the purpose of Islamic jurisprudence. Islamic jurisprudence expects protection of faith, life, reason, race and property from humans for the humans. Protection and prevalence of theses five purposes is called peace in Islamic jurisprudence. In the religion of our world, there are two ways of acquisition of peace, eradication of crimes and protection of property, First awareness and fright of divine punishments on committing a sin or sins, Secondly, to punish the wrong doer on the basis of the nature of his/her crime in the circle of pure justice. These worldly punishments have remained different in different ages and religions while in our modern world and revolted era, punishments of Islamic Jurisprudence are considered stick and against the humans rights, especially punishments relating to adultery and fornication. It is therefore, considered imperative to compare these punishment relating to adultery and fornication , we have in our Islamic jurisprudence to those of other religion in order to unearth the relating of considering Islamic punishments strict and against the human rights.